Minimum chip thickness in machining MEMS structure using Tool Based Micromilling - Ali, Mohammad Yeakub; Mass Duki, Siti Hamizah; Mansor, Noor Adila (2011)
Tool based micromilling is a promising micromanufacturing technology to produce miniaturized features of about 25μm in size frMEMS and Bio-MEMS applications.It is the most flexible and the fastest way to produce complex three dimensional microcomponents including sharp edges with surface finish at a reasonble cost.Moreover,it is capable of machining a broader range of materials such as engineering plastics, aluminium, titanium, etc. However,the issue in tool based micromilling is the minimum chip thickness which is often between5-30% of the tool edge radius. No chip will form if the depth of cut cannot achieve the minimum chip thickness value.The lack of control on minimum chip thickness often leads to the coarse machined surface, poor machining accuracy and difficult in chip removal from the machining zone which leads to burrformation.Hence, the chip formation mechanism should be studied deeply to avoid these problems.In this research WC was elected for tool material and Aluminium Alloy 1100 for work material for the investigation of minimum chip thickness.The experiment is being conducted on a miniature machine known as Microtools Integrated Multi-purpose machine modelled DT-110.The value of chip thickness produced by tool 4.8μmwith3mm/min feedrate,3000rpm cutting speed and 5μm depth of cut.The minimum chip thickness is useful for machining Micro electromechanical System(MEMS) and Bio-MEMSstructures.